Lama Penggunaan KB Suntik 3 Bulan Signifikan Meningkatkan Resiko Gangguan Menstruasi di TPMB Widya Putri - Yuanisa Desi Ramadhani; Ellyda Rizki Wijhati (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Menstrual irregularities may arise after long-term use of injectable contraception. Menstrual disorders are characterized by abnormal bleeding during the menstrual cycle, as shown by the duration of the monthly cycle, the length of the menstrual period, and the volume of menstrual blood. Changes in the menstrual cycle affect physical, psychological, social, and spiritual dimensions, reduce the quality of life, and may lead to long-term problems if inadequately managed. Prolonged use of tri-monthly injectable contraceptives is recognized to cause changes in the levels of estrogen and progesterone hormones within the body. This impairs endometrial function and results in histological changes that cause menstrual problems. This study aims to determine the relationship between the length of usage of three-monthly injectable contraceptives and abnormal menstruation at TPMB (Independent Midwifery Practice) Widya Puri. This research employed an analytical study utilizing a cross-sectional methodology. The study sample comprised of 100 mothers attending a follow-up appointment for a three-monthly injectable contraception. The methodology employed was purposive sampling. Data collecting methods employed questionnaires and observation sheets, which were analyzed using univariate analysis and chi-square tests. The data showed that 84 mothers, representing 84.0%, had a duration of use more than one year. The majority of responders encountered menstruation problems. Amenorrhea occurred in 55 individuals (55.0%), while menstrual problems were the least prevalent. Hypomenorrhea occurs in 6 individuals, representing 6% of the population. The statistical analysis employing the Chi Square test obtained a p-value of 0.000 (<0.05). This is a significant relationship between the duration of 3-month injectable contraceptive use and menstrual problems. In this case, it may be stated that the research hypothesis Ha is accepted whereas Ho is rejected, therefore confirming the validity of the research hypothesis. Furthermore, it may be inferred that a relationship exists between the duration of 3-month injectable contraceptive usage and menstruation disorders in TPMB Widya Puri.